Identifikasi kandungan ikan tenggiri (Scomberomorus commerson) dan ikan sapu-sapu (Pterygoplichthys sp) pada otak-otak: Identification of mackerel (Scomberomorus commerson) and suckermouth catfish (Pterygoplichthys sp) in otak-otak - Dedy Suseno; Intan Razari (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2023)
Mackerel fish is commonly used in the manufacturing of otak-otak. Authentication of fish-based food products by visual method is not possible so counterfeiting or mislabeling in these products is very likely to occur. Suckermouth catfish meat can also be used as a raw material for fish-based products because it contains high protein content. However, the source of suckermouth catfish taken from the Ciliwung River has the potential to contain heavy metals such as Pb, Cd, Hg, Sn, and As. The purpose of this study was to analyze the content of mackerel and suckermouth catfish in otak-otak, and identify the presence of heavy metal content in otak-otak samples containing suckermouth catfish. Nineteen otak-otak samples analyzed with 3 samples wrote the description of mackerel on the packaging. DNA analysis of suckermouth catfish and mackerel in otak-otak using Polymerase Chain Reaction (PCR) methods that use a specific primer. Analysis of heavy metals using the Atomic Absorption Spectrophotometry (AAS) method. Twelve of the nineteen samples identified a 423 bp band in the electrophoresis gel. The band was confirmed belonging to the suckermouth catfish species after analysis using sanger sequencing methods. Nine of the nineteen samples showed a 238 bp band that corresponded to mackerel. A total of 12 otak-otak samples were identified as containing suckermouth catfish, 11 of which contained Pb metal with a concentration of <0.034 mg/kg and 1 sample containing Pb metal with a concentration of 0.34 mg/kg. The presence of heavy metal content in the otak-otak samples whose concentration exceeds the maximum limit makes this otak-otak can’t halalan thayyiban for consumption.